Prominence in Indonesian Stress, phrases, and boundaries - van Zanten, Ellen; Goedemans, Rob (Wacana, Journal of the Humanities of Indonesia, 2009)
Many (Western) languages have word-based stress, which entails that one, predictable syllable per word is more prominent than all the other syllables in that word. Some linguists claim that such stresses also occur in Indonesian. In this article, we set out to investigate that claim using experimental, phonetic methods. The results confirm our hypothesis that Indonesian lacks word-based stress. Yet, we do observe some kind of prominence pattern. In the last part of this article, we search for the phonological phenomenon that generates this pattern, exploring the level of the phrase to see whether phrasal accents or boundary markers are likely candidates.